Sigma phase-induced failure of AISI 310 stainless steel radiant tubes. (December 2017) - Bahrami, Abbas; Ashrafi, Ali; Rafiaei, Seyed Mahdi; Mehr, Maryam Yazdan
Abstract: Failure of AISI 310 stainless steel tubes, used as radiant tubes in a heat treatment furnace, operating at temperature range 480 to 700 °C, is investigated. Longitudinal cracks were observed in tubes after around five years of operation. Optical microscope, scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) were used to analyze the observed failure. Results revealed that the failure is due to the formation of sigma phase. Sigma phase formation is accompanied with loss of ductility and formation of voids and subsequently cracks. Possible reasons for the formation of sigma phase, its implications for the mechanical integrity of the tubes, and strategies to avoid observed failure in similar cases are presented and discussed in this paper. Highlights: Failure analysis of AISI 310 stainless steel radiant tubes is performed. Sigma phase formation is found to be the major cause of failure. Sigma phase formation is accompanied with loss of ductility and formation of voids and cracks in the microstructure. The correlations between the microstructure and observed failure are discussed.